GAMBARAN TINGKAT KEPUASAN PELAYANAN PADA PASIEN BPJS PBI DAN PASIEN BPJS NON PBI YANG DIRAWAT DI KELAS III RUMAH SAKIT PKU MUHAMMADIYAH GOMBONG - Siti Mastuti; Febriana Nurul; Kusumastuti Kusumastuti (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2021)
Background : Patient satisfaction is the main thing that is considered in providing services. The success of the services provided in a health facility is the level of patient satisfaction. The Ministry of Health of the Republic of Indonesia believes that the Social Security Organizing Body (BPJS) is a public legal entity created to carry out social security programs. BPJS Kesehatan participants are divided into two, the first is poor people who receive contribution assistance (PBI) and the second is Non PBI participants who are participants who receive wages (PPU), participants who do not receive wages (PBPU) and are not workers whose costs are borne alone or collectively to BPJS Health.Objective : To know the description of the level of service satisfaction in BPJS PBI patients and BPJS Non PBI patients who are treated in class III PKU Muhammadiyah Gombong Hospital.Research Methods : This research is used a descriptive quantitative research design with a cross sectional approach. The population in this study was BPJS PBI 767 patients and BPJS Non PBI 106 patients. Sampling used probability sampling as many as 20 BPJS PBI patients and 10 Non PBI BPJS patients. Data were analyzed by univariate.Results : There is shows the results on the characteristics of BPJS PBI patients with the most sex, namely 16 women (80%), the majority of high school education level is 8 people (40%) and BPJS Non PBI, the most gender is 6 men (60 %), the level of education at most SMP 5 people (50%). The results of the BPJS PBI patients showed 11 people (55%) out of 20 respondents chose the satisfied category and the BPJS Non PBI patients showed 9 people (90%) out of 10 respondents chose the very satisfied category.Recommendations : The results of this study are expected to be a reference or reference in overcoming existing problems and improving quality in terms of services and as additional knowledge about the use of health services in hospitals.